Cutaneous Involvement in Waldenström's Macroglobulinaemia - Sarah Stien; Eric Durot; Anne Durlach; Marie Beylot-Barry; Henri Adamski; Helmut Beltraminelli; Gérôme Bohelay; Agnès Carlotti; Olivier Carpentier; Pascale Cornillet; Romain Dubois; Nathalie Franck; et al. (Medical Journals Sweden, 2020)
Cutaneous involvement in Waldenström's macroglobulinaemia (WM) has been poorly characterized. To describe this involvement, a retrospective study of 19 patients with WM and cutaneous involvement of tumour B cells was performed. Twelve patients (group 1) had lymphoplasmacytic, non-transformed cutaneous proliferation, while in 7 cases (group 2) cutaneous involvement corresponded to histological transformation. In group 1, skin involvement was inaugural in 6 cases. The lesions were infiltrated plaques (83%), papules (25%) and tumours (42%). Four patients had a similar clinical picture (purplish, bilateral and symmetrical infiltration on the face). MYD88 L265P mutation was detected in the skin biopsy in all 6 cases tested. The 3-year specific survival rate was 88%. In group 2, cutaneous transformation occurred during the follow-up of the WM (71%). Lesions presented as ulcerated tumours (86%) of the trunk (57%) and lower limbs (57%). The 3-year specific survival rate was 22%. Skin involvement in WM has distinctive characteristics (e.g. clinical, histological, immunohistochemical, MYD88 L265P mutation).